Complement System and Alarmin HMGB1 Crosstalk: For Better or Worse - Gaboriaud, Christine; Lorvellec, Marie; Rossi, Véronique; Dumestre-Pérard, Chantal; Thielens, Nicole M. (Frontiers in Immunology, 2022)
Our immune system responds to infectious (PAMPs) and tissue damage (DAMPs) signals. The complement system and alarmin High-Mobility Group Box 1 (HMGB1) are two powerful soluble actors of human host defense and immune surveillance. These systems involve molecular cascades and amplification loops for their signaling or activation. Initially activated as alarm raising systems, their function can be switched by regulatory mechanisms towards inflammation resolution, where they sustain immune maturation and orchestrate repair mechanisms opening the way back to homeostasis. However, these systems are often referred to as double edge swords, because molecular imbalance or mis regulation can lead to deleterious effects, including severe cellular and tissue injury. For example, dysregulation or excessive activation of the complement system (due to host genetic or pathological virulence factors) can drive or exacerbate numerous inflammatory disorders such as cancer, lupus nephritis, periodontitis, Alzheimer’s disease, etc... Friend or foe? The answer to this question actually depends on the specific tissue and disease context. Indeed, cellular environments and molecular receptors vary greatly for different cells and tissues, and thus specific physiological or pathological roles will occur depending on the tissue and cellular contexts. Recent studies suggest a crosstalk between the alarmin HMGB1 and the complement C1 subunits at different levels. Indeed, HMGB1 together with the complement component C1q can modulate macrophage polarization and metabolism; HMGB1 can also trigger the activation of the complement classical pathway in an antibody-independent manner; and the complement component C1s is able to cleave HMGB1. However, many unknowns and questions remain on the underlying mechanisms, especially regarding the fragile molecular balance which can drift towards disease or return to homeostasis. We briefly introduce these two systems, how they function and interact at the molecular level (when elucidated) and provide examples of diseases to illustrate the signs and consequences of their roles and interaction. Current issues and future challenges are briefly discussed at the end.